PROTECTING THE CONFIDENTIALITY OF DATA TRANSMISSION AND RECEIPT AT THE SECURITY OPERATIONS CENTRE USING MACHINE-TO-MACHINE (M2M) COMMUNICATION METHODS - MARCHENKO, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The development and improvement of privacy protection technologies for data transmission and receipt is driven by the use of modern technologies that include digital equipment and auxiliary electronic media for collecting, processing and displaying information (sensors, peripherals) that can use machine-to-machine (M2M) methods for data processing by the data centre (SOC).The paper describes the main potential problems and challenges that may arise between the M2M technology and the security centre during the transmission and processing of data using M2M devices. On the basis of the analysed problems and challenges, measures to prevent threats with violation of confidentiality and data integrity are formed. In order to minimise data security threats, security measures have been developed, based on which the following were investigated: basic authorisation operations (identification, classification, authentication and data encryption); data protection and confidentiality issues with a study of the impact of DoS attacks on the M2M device system; use of software for the M2M system and SOC; M2M system planning and planning recommendations. The study investigated the main key parameters for identifying security problems in the transmission and receipt of data between M2M devices and the equipment of the security centre. Based on the literature review, the key aspects of M2M technology were analysed, where the paper addressed the issues of authorisation, encryption, monitoring, software use and scheduling. Network security threats are considered, namely: data leakage, unauthorised access, insufficient monitoring of the network and SOC systems, use of outdated and unupdated software, legal restrictions, technical circumstances from the engineering point of view. The research results showed that some research machines were subjected to DoS attacks by intruders, which indicates the search for new opportunities and methods to protect data confidentiality.